The purchasing and supply manager's guide to the C.P.M. exam - Sollish, Fred.; Semanik, John. (San Francisco : Harbor Light Press, 2005)
Real World Scenarios for Practical Insights into the Field of Purchasing and Supply Management Whether you're a purchasing or supply management professional seeking to validate the skills and knowledge acquired through years of practical experience, or a relative newcomer to the field looking to strengthen your resume, the C.P.M. certification from the Institute for Supply Management (ISM) provides you with the means to do so. The Purchasing and Supply Manager's Guide to the C.P.M. Exam was developed to help you prepare for the four modules that comprise the C.P.M. exam, and includes
Disposition Surplus Assets
Description based upon print version of record.
English
Includes bibliographical references (p. 400-403) and index.
Keywords: Purchasing -- Examinations -- Study guides; Industrial procurement -- Examinations -- Study guides